HOLISTIC EDUCATION INTERVENTIONS: INTEGRATING ISLAMIC VALUES IN SCHOOL GUIDANCE AND COUNSELING TO OVERCOME LEARNING - Herlinda, Fitra; Munir; Nurhasnawati (EDUCATIONE, 2025)
This study is grounded in the recognition that guidance and counseling (BK) play a pivotal role in addressing students’ learning problems, which can significantly affect both academic achievement and personal development. The integration of Islamic educational values into counseling services is seen as a promising approach to holistically resolve such issues, especially in contexts where moral, spiritual, and ethical guidance is essential. The primary objective of this research is to explore and optimize the effectiveness of guidance and counseling when integrated with Islamic education principles in overcoming students’ learning problems. Employing a library research method, this study systematically collects, reviews, and synthesizes scholarly literature, including books, journal articles, and empirical reports, to build a comprehensive understanding of the relevant theories and practices. The findings indicate that the incorporation of Islamic values—such as patience, honesty, discipline, sincerity, and responsibility—not only increases students’ motivation and engagement but also strengthens character and psychological resilience. Moreover, integrated counseling practices have been shown to improve student attendance, classroom behavior, and homework completion rates, as evidenced by case studies in Islamic schools. In conclusion, this research contributes to the field by highlighting the value of a holistic, spiritually-grounded counseling model that supports both academic and moral growth. The study’s practical implications include the need for ongoing counselor training, collaboration among stakeholders, and systematic evaluation. Future research is recommended to examine the long-term effects of this integrative approach and adapt it for diverse educational settings.